2007
DOI: 10.1002/em.20277
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic activity of overnight urine from healthy non‐smoking subjects

Abstract: Urinary mutagenicity was evaluated in relation to environmental mutagen exposure (i.e., diet, indoor/outdoor activities, residential area etc.) on the day prior to sample collection, and also considering factors that contribute to the variability of Salmonella mutagenicity assay results. Overnight urine samples from 283 healthy non-smoking residents of northeast Italy (46% males, 20-62 years) were analyzed for mutagenicity on sensitive Salmonella typhimurium strain YG1024 with S9 mix employing the preincubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…All subjects were noncurrent smokers, defined as former smokers who had stopped smoking at least one year before sample collection or those who had never smoked. Urine analysis of nicotine and its metabolites 29 confirmed that all subjects were nonexposed to tobacco smoke as they had urine nicotine concentrations <0.01 mg/mmol creatinine.…”
Section: Methodsmentioning
confidence: 86%
“…All subjects were noncurrent smokers, defined as former smokers who had stopped smoking at least one year before sample collection or those who had never smoked. Urine analysis of nicotine and its metabolites 29 confirmed that all subjects were nonexposed to tobacco smoke as they had urine nicotine concentrations <0.01 mg/mmol creatinine.…”
Section: Methodsmentioning
confidence: 86%
“…42 Pavanello et al used HPLCfluorescence to analyze BaP-tetraol released from DNA of lymphomonocytes and reported their presence in 248 out of 585 subjects at a mean level of 1.28 ± 2.80 adducts per 10 8 nucleotides. 43 Mensing et al also reported BaP-tetraol released from white blood cells as determined by HPLC-fluorescence with levels in the range of 1−2 adducts per 10 8 nucleotides. 44 These contrasting results between studies using mass spectrometric techniques versus those using HPLC-fluorescence to analyze BaP-tetraols released from DNA upon acid hydrolysis are difficult to reconcile.…”
Section: ■ Discussionmentioning
confidence: 96%
“… 30 The source of the high variability of the urine mutagenicity values is likely due to (1) the relative high sensitivity of this assay to diet, as previously reported, 31 even in nonsmokers, (2) individual metabolic differences, and (3) variability of the cellular-based assay itself. 32 …”
Section: Discussionmentioning
confidence: 99%